Vitamin D and cardio-metabolic biomarkers: small-scale comparative study between Libyan migrants and resident women in Serbia. Issue 1 (1st January 2019) - Vidovic, Nevena; Faid, Fathia; Pantovic, Ana; Nikolic, Marina; Debeljak-Martacic, Jasmina; Zekovic, Milica; Milesevic, Jelena; Drah, Mustafa Mohamed; Zec, Manja
ABSTRACT: Libyan women are at high risk of vitamin D deficiency, mostly due to their lifestyle and low exposure to sun. In the last decades, Libyan residents have been forced to seek refuge in countries such as Serbia, a country with high incidence of cardio-metabolic diseases. Serbian residents tend to be deficient in vitamin D, mostly due to the lack of vitamin D fortification policy. The aim of this study was to evaluate vitamin D status in Libyan adult women migrating to Serbia, with the assessment of cardio-metabolic and nutritional biomarkers, including erythrocytes fatty acid composition, magnesium concentration, and dietary intake. The same markers were measured in Serbian women, and comparisons between the groups were made. Despite low vitamin D dietary intake in both study groups, we observed lower plasma vitamin D status in Libyan women. This was accompanied by a significantly lower concentration of magnesium in Libyan women. Libyan women had significantly higher omega-3 index and lower n-6/n-3 ratio in erythrocytes' phospholipids. We observed significant negative correlation between vitamin D and n-6 polyunsaturated fatty acids (PUFA) concentrations in both study groups. Despite lower vitamin D status in the Libyan group, erythrocyte fatty acid composition, along with blood lipids' concentrations, indicated a lower cardiovascular risk. Based on our results, the discrepancy in the vitamin D status could not be ascribed to the participants' dietary intake of the micronutrient, rather is potentially associated with ethnic-specific cardio-metabolic profile, which should be confirmed in larger cohorts.